Evaluation of Silicone as an Artificial Lubricant in Osteoarthrotic Joints. Issue 5758 (15th May 1971) - Wright, V.; Haslock, D. I.; Dowson, D.; Seller, P. C.; Reeves, B.
Abstract : Silicone 300 has been evaluated as an artificial lubricant in osteoarthrotic joints by means of a pilot study in five inpatients and a control trial of 25 outpatients with 40 osteoarthrotic knees. Sequential analysis showed a significant benefit from saline compared with silicone at one week follow-up and no significant difference at one month. Measurement of stiffness with a knee arthrograph showed no difference in reduction of stiffness between the two substances. In a study of 18 rabbits there was no evidence that silicone was retained in the joint cavity for longer than 48 hours. There was a failure of clearance of iodinated serum albumin for as long as three to four days after the injection of silicone, suggesting some obstruction to lymphatic outflow. Experimentally produced cartilaginous defects did not heal quicker with the injection of silicone into the joint.